A Fractured Landscape of Modernity - Wilkes, J. author. aut Link
IX, 193 p.
Keywords: This book uses the contradictions, fractures and coincidences of a twentieth-century rural landscape to explore new methods of writing place beyond 'new nature writing'. In doing so it opens up new ways of reading modernist artists and writers such as Vanessa Bell, Mary Butts and Paul Nash.